PENERAPAN MODEL INDEX CARD MATCH BERBANTUAN MEDIA FLIPCHART UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VIII SMP NEGERI 1 KAMBERA - Saputri Karanja Ngana, Enjelika; Makaborang, Yohana; Meissy Matulessy, Yoin (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study is to describe students’ cognitive and affective learning outcomes as well as the improvement in learning outcomes at SMP Negeri 1 Kambera after implementing the Index Card Match model assisted by flipchart media. This research is a Classroom Action Research (CAR) using a descriptive quantitative approach. The subjects of this study were eighth-grade students of SMP Negeri 1 Kambera. Data collection instruments consisted of observation sheets and written tests. The results of this study show a significant improvement in cognitive learning outcomes, increasing from 27% in the pre-cycle to 60% in cycle I, and then increasing further to 87% in cycle II. Therefore, it can be concluded that the implementation of the Index Card Match model assisted by flipchart media can improve the learning outcomes of eighth-grade students at SMP Negeri 1 Kambera.